2015
DOI: 10.1124/dmd.114.061325
|View full text |Cite
|
Sign up to set email alerts
|

No Contribution of the ABCB11 p.444A Polymorphism in Japanese Patients with Drug-Induced Cholestasis

Abstract: European studies have revealed that the ABCB11 c.1331T>C (V444A) polymorphism (rs2287622) C-allele frequency is higher among patients with drug-induced cholestasis. Given the low incidence of this disease, however, this association has not been sufficiently elucidated. We aimed to investigate the significance of this polymorphism in Japanese patients. We determined ABCB11 V444A polymorphism frequencies and HLA genotypes in two independent drug-induced cholestasis cohorts. Expression and taurocholate transport … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 29 publications
1
9
0
Order By: Relevance
“…Previous studies have identified a common BSEP polymorphism V44A (1331T > C, rs2287622) as genetic risk factor for DILI in Caucasian1011 In the present study, we tested the same SNP in Chinese patients, however, no significant association was found between rs2287622 polymorphism and the development of DILI, which was similar to the study conducted in Japan13. Since genetic associations were ethnicity-specific and drug-specific, the association of ABCB11 rs2287622 genetic variations and DILI should be investigated in other populations and other drugs.…”
Section: Discussionsupporting
confidence: 81%
“…Previous studies have identified a common BSEP polymorphism V44A (1331T > C, rs2287622) as genetic risk factor for DILI in Caucasian1011 In the present study, we tested the same SNP in Chinese patients, however, no significant association was found between rs2287622 polymorphism and the development of DILI, which was similar to the study conducted in Japan13. Since genetic associations were ethnicity-specific and drug-specific, the association of ABCB11 rs2287622 genetic variations and DILI should be investigated in other populations and other drugs.…”
Section: Discussionsupporting
confidence: 81%
“…However, conflicting reports exist (87) and additional studies in larger and varied populations are needed to validate these findings.…”
Section: Risk Factorsmentioning
confidence: 99%
“…19 Similar findings also were reported in European and Caucasian populations, 29 however, no statistically significant association was reported in studies conducted in Chinese and Japanese cohorts. 21,35 The 444A variant of BSEP also has been identified as a risk factor for the development of ICP, with the variant being more frequent in ICP patients when compared to pregnant controls. 8,20,36 Dixon et al reported an increased risk of ICP in subjects with the 444A variant, especially those who were homozygous for this BSEP variant.…”
Section: Discussionmentioning
confidence: 99%
“…8,20 However, a similar study in a Japanese population found no association of cholestasis with this variant. 21 Studies to explain the mechanistic basis for this increased susceptibility to acquired cholestatic syndromes have been unsuccessful. The expression of the variant BSEP is slightly lower in both liver tissue 22 and in transfected systems.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation